Structurally improved reduced graphene oxide nanocluster structured assembly with Naringin for the effective photothermal therapy of colon tumour patients and nursing care management. (17th August 2020) - Han, Liwei; Tan, Juan; Li, Jing; Meng, Tianyu; Wang, Yuhang; Wang, Sisi
Abstract : Functionalization of naringin (Nar) on a nanomaterials surface will decrease their detrimental side effects and escape them from immunological rejection. In this study, we developed a sustainable green chemistry route to fabricate naringin-reduced graphene oxide nanosheets (rGO@Nar) through the easy method. The hydroxyl group of Naringin reduces and generates the functionalization of rGO@Nar, and it was confirmed through various spectroscopic method (FT-IR and Raman) and electroscopic methods (FE-SEM and HR-TEM). After careful evaluation of the nanocomposion, we performed cancer cell growth inhibition properties of the colon cancer cell line and Human vein endothelial cells (HT-29 and HUVEC). Also, we performed the photothermal effects of these nanocomposites on cell proliferation and apoptosis using different biochemical staining. Our in vitro investigational datas are established rGO@Nar effectively exhibited and also with rGO@Nar + NIR the photothermal conversion therapy improved prostate cancer cells abolishing the cancer cells. More interestingly rGO@Nar + NIR was found to surpass the activity of rGO@Nar in colon cancer cells tested a topnotches. Thus, our study suggests that rGO@Nar + NIR could be used as impending anticancer candidate for photothermal ablation of prostate cancer cells. Further examinations of the mechanism indicated that anticancer activity was accomplished by inducing apoptosis in cancer cells. GRAPHICAL ABSTRACT: UF0001